Analysis of Students' Mathematical Reasoning in Solving Story Problems According to Polya's Steps - alfina; Maftukhah Rosyada; Rusmalinda Gustia; Inarotul Wafiroh; Fatimatus Solikha; Ratri Rahayu (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2024)
The purpose of this study was to analyze the ability of mathematical reasoning in solving story problems according to Polya's steps. This study is a qualitative descriptive study. Data collection techniques were interviews, observations and mathematical reasoning tests. The research instrument used mathematical reasoning test questions in the form of 6 reasoning questions based on multiplication story problems, interview sheets, and observation sheets. The subject in this study was one fourth grade student of SDN 3 Bulung Kulon in the high category. The results showed that students in the high category could complete all indicators of mathematical reasoning completely by using Polya's steps, namely understanding the problem, planning problem solving, implementing problem solving planning, and rechecking the answers.